Combining Cryptography with Steganography - Gencoglu, Muharrem Tuncay (E D P Sciences, 2017)
In this paper a different cryptographic method is introduced by using Power series transform, codes of ASCII and science of steganography. Here, we produce a new algorithm for cryptology, we use Expanded Laplace transformation of the exponential function for encrypting the plain text and we use codes of ASCII for support to the confidentiality of the chipertext. After, Chipertext have embedded by steganographic method in another plaintext to hide the existence of chipertext. We show corresponding inverse of Power Series transform for decryption.
2nd International Conference on Computational Mathematics and Engineering Sciences (CMES) -- MAY 20-22, 2017 -- Istanbul, TURKEY
Keywords: Cryptology; Encryption; Decryption; Laplace Transform; ASCII; Steganography